Tele-ophthalmology for screening for eye diseases in older patients with cognitive complaints. (September 2021) - Boureau, Anne-Sophie; Masse, Helene; Chapelet, Guillaume; de Decker, Laure; Chevalet, Pascal; Pichierri, Sophie; Weber, Michel; Berrut, Gilles
Introduction: Population-based studies show a significant increase in the prevalence of visual impairment in older patients. However, older patients and patients with lower Mini-Mental State Examination (MMSE) scores have few ophthalmological assessments. The main objective of our study was to evaluate the feasibility of tele-ophthalmological screening for ophthalmological diseases in older patients referred for cognitive assessment. Methods: This monocentric prospective study included patients referred to a memory clinic for cognitive assessment. All patients underwent a geriatric assessment comprising a cognitive assessment associated with tele-ophthalmological screening undertaken by an orthoptist, including undilated retinal photography. The retinal photographs were subsequently sent to an ophthalmologist. We identified patients who were not eligible for ophthalmological assessment, for patients that had to come back due to poor-quality retinal photographs and finally for detected eye diseases. The association between the geriatric variable and newly detected eye diseases was analysed in univariable and multivariable analyses. Results: The mean age of the 298 patients included was 83.5 years  ± 5.65; 29.5% were male. The mean MMSE score was 20.8 ± 5.2; 66.3% of patients had a diagnosis of dementia. Eighteen patients (6.0%) were not eligible for ophthalmological examination and 13 patients (4.6%) were asked to come back owing to poor-quality retinal photographs. Forty-one patients (13.7%) had a newly detected eye disease. In multivariable analysis, patients with a lower MMSE had significantly more newly identified eye diseases. Discussion: The tele-ophthalmological screening method identified unknown ophthalmological diseases requiring specialised management in this older population with cognitive complaints.